Corporate Finance & Investments: Corporate Finance Issues Prevailing In India at Present - Kumar, Dhiresh; Mishra, Krishna Kant (International Research Journal of Management, IT & Social Sciences, 2016)
The subject of corporate finance has assumed tremendous significance in the light of the ongoing economic uncertainty across the world. Apart from the three most important decisions of fund raising, fund deployment and generation of returns, greater emphasis has been laid down upon creating a long term value through Economic value addition (EVA). The role of assets in generation of cash flows has become even more pronounced in modern day changing dynamics. More than the external factors, India has certain homegrown structural problems which seriously needs to be addressed at this juncture; the prominent ones being ensuring a high ICOR and addressing the supply side bottlenecks in the economy. Indian companies will have to address the financial problems in the light of the current macroeconomic turmoil of high inflation and revised growth projection of 5%. This has to be done despite having a sound corporate financial framework. This paper attempts to address these problems and tries to suggest some solution to overcome the period of uncertainty